2013
DOI: 10.1111/aor.12229
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of the Apico Aortic Blood Pump: Anatomical Positioning, Hydrodynamic Performance, Hemolysis Studies, and Analysis in a Hybrid Cardiovascular Simulator

Abstract: The Apico Aortic Blood Pump (AABP) is a centrifugal continuous flow left ventricular assist device (LVAD) with ceramic bearings. The device is in the initial development phase and is being designed to be attached directly to the left ventricular apex by introducing an inlet cannula. This paper reports results from in vitro experiments. In order to evaluate implantation procedures and device dimensioning, in vitro experiments included an anatomic positioning study for the analysis of surgical implantation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This LVAD was designed to be attached directly to the left ventricular apex and connected to the aorta through an outlet cannula. 30 Centrifugal blood pumps allow: operation at lower speed motor (approximately 2000 rpm) than axial pumps (approximately 10 000 rpm); lower rates of hemolysis, that is, less damage to blood elements; anatomically compatible dimensions and reach the estimated service life of more than 2 years of mechanical support, as bridge to transplant. Measured hemolysis mean normalized index in the AABP was 0.009 g/100 L (±0.002 g/100 L).…”
Section: Centrifugal Blood Pumpmentioning
confidence: 99%
See 2 more Smart Citations
“…This LVAD was designed to be attached directly to the left ventricular apex and connected to the aorta through an outlet cannula. 30 Centrifugal blood pumps allow: operation at lower speed motor (approximately 2000 rpm) than axial pumps (approximately 10 000 rpm); lower rates of hemolysis, that is, less damage to blood elements; anatomically compatible dimensions and reach the estimated service life of more than 2 years of mechanical support, as bridge to transplant. Measured hemolysis mean normalized index in the AABP was 0.009 g/100 L (±0.002 g/100 L).…”
Section: Centrifugal Blood Pumpmentioning
confidence: 99%
“…Measured hemolysis mean normalized index in the AABP was 0.009 g/100 L (±0.002 g/100 L). [30][31][32] Figure 1 shows the AABP's hydrodynamic performance. Figure 2 shows the AABP's electrical performance.…”
Section: Centrifugal Blood Pumpmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial concept of AABP development has been included several studies. In 2012, Silva et al 1,2 presented AABP's concept validation through in vitro tests including impeller geometry and hydrodynamic performance optimization, hemolysis assessment, anatomical positioning, and analysis in a cardiovascular simulator. Those studies indicated a satisfactory device performance for its use as a LVAD.…”
Section: Introductionmentioning
confidence: 99%
“…The assembled dynamometer measured torque and mechanical power to validate numerical simulations and analytical calculation. [25][26][27][28][29] Figure 7 shows the experimental setup.…”
Section: Resultsmentioning
confidence: 99%